2022
DOI: 10.1108/ejm-03-2022-0173
|View full text |Cite
|
Sign up to set email alerts
|

Do salespeople’s online profile pictures predict the number of online reviews? Effect of a babyface

Abstract: Purpose This study aims to investigate the impact of a salesperson’s babyface in his/her profile picture on the number of online reviews the salesperson receives. In addition to testing the direct relationship, this study explores the moderating roles of salesperson gender and consumer involvement. Design/methodology/approach Responding to the call for field-based consumer research, the authors test their theory using an experimental design and a field study. Study 1 employs an experimental design in high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Previous studies on cuteness have shown that the effects of cuteness can be moderated by a person's trait (Wang et al , 2017), gender (Li and Yan, 2021) and service types (Yim et al , 2022). Future research could explore different moderators, such as specific AI assistants or product categories, that might affect the cuteness effects on trustworthiness and attachment in the AI context.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on cuteness have shown that the effects of cuteness can be moderated by a person's trait (Wang et al , 2017), gender (Li and Yan, 2021) and service types (Yim et al , 2022). Future research could explore different moderators, such as specific AI assistants or product categories, that might affect the cuteness effects on trustworthiness and attachment in the AI context.…”
Section: Discussionmentioning
confidence: 99%
“…In the fourth article, Yim et al (2022) examine the relationship between the extent to which salespeople have a babyface in their profile pictures and the number of online reviews they receive, also looking at important boundary conditions such as consumer involvement and salesperson gender. Using an experimental design and field data from online profile pictures of real estate agents combined with an application interface of facial recognition based on artificial intelligence, the authors find that salespeople with a babyface get fewer (more) online reviews in high-involvement (low-involvement) service settings, but that the negative effect of a babyface on the number of online reviews is less (more) severe among female (male) salespeople.…”
Section: Special Issue Articlesmentioning
confidence: 99%
“…As evidenced from the articles included in this special issue, field studies can be conducted in a wide range of shopping environments, capturing multiple key customer outcomes, including but not restricted to customer switching (de Mesquita et al , 2023), customers’ purchase likelihood and the amount of money spent in a store (Otterbring et al , 2022), clickthrough rates of online ads (Isojärvi and Aspara, 2023) and the number of online reviews written by customers (Yim et al , 2022). Moreover, such field-based investigations are not restricted to traditional physical commercial settings but can be effectively run in a variety of digitally enabled environments.…”
Section: Concluding Remarks and Study Checklistmentioning
confidence: 99%
“…Studies show that a more mature physical interface can lead the consumers to purchase high involvement services to the detriment of low involvement services. The physical appearance is shown as an important characteristic in how a consumer examines the authority or knowledge of its discussion partner (Yim, 2022).…”
Section: Gender Characteristics At Ai and Robotsmentioning
confidence: 99%